Split Local Artificial Boundary Conditions for the Two-Dimensional Sine-Gordon Equation on R2 (Communications in Computational Physics, 2011)
In this paper the numerical solution of the two-dimensional sine-Gordonequation is studied. Split local artificial boundary conditions are obtained by the operatorsplitting method. Then the original problem is reduced to an initial boundaryvalue problem on a bounded computational domain, which can be solved by the finitedifference method. Several numerical examples are provided to demonstrate the effectivenessand accuracy of the proposed method, and some interesting propagation andcollision behaviors of the solitary wave solutions are observed.